2020
DOI: 10.1111/efp.12588
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather variables and season on sporulation of Phytophthora pluvialis and Phytophthora kernoviae

Abstract: Phytophthora pluvialis and Phytophthora kernoviae are the causal agents of important needle diseases on Pinus radiata in New Zealand. Little is known about the epidemiology of the diseases, making the development of control strategies challenging. To investigate the seasonality and climatic drivers of sporulation, inoculum traps, consisting of pine fascicles floating on water in plastic containers, were exchanged fortnightly at five sites in P. radiata plantations between February 2012 and December 2014. Secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 34 publications
6
25
1
Order By: Relevance
“…In the latter, P. austrocedri was expected, but none were detected at this site. However, the detection of P. kernoviae close to a healthy Scots pine needs to be followed up, as recently, P. pluvialis and P. kernoviae have been associated with needle diseases of Pinus radiata in New Zealand [89], and this could be an emerging problem on pine.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, P. austrocedri was expected, but none were detected at this site. However, the detection of P. kernoviae close to a healthy Scots pine needs to be followed up, as recently, P. pluvialis and P. kernoviae have been associated with needle diseases of Pinus radiata in New Zealand [89], and this could be an emerging problem on pine.…”
Section: Discussionmentioning
confidence: 99%
“…Peak abundance for both species was in late winter, approximately coincident with maximum disease expression nationally. Accordingly, probability of detection of inoculum was related to lower temperatures and periods of wet weather (Fraser et al 2020). Similarly, preliminary small-scale studies with potted grafted cuttings have revealed successful intermittent infection at least between July and October (mid-winter and mid-spring; Hood et al 2017).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, field research has been conducted to determine the seasonal life cycles of both Phytophthora species. Between 2012 and 2014 spore traps consisting of freshly detached radiata pine fascicles floating on deionised or rainwater held in plastic containers were placed at fortnightly intervals beneath initially symptomatic radiata pine stands (Fraser et al 2020). In the laboratory, sections of the needle baits were plated onto selective isolation media to establish the presence and identity of trapped phytophthoras.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another, “red needle cast,” has been associated mainly with Phytophthora pluvialis Reeser, Sutton & Hansen, and to a lesser extent with P . kernoviae (Fraser et al, 2020 ). Such weather, with temperatures allowing growth but with low insolation restricting photosynthesis, is likely to deplete the carbohydrate reserves that would help the host resist pathogens.…”
Section: Seasonal Phenologymentioning
confidence: 99%